The Impact of Environmental Communication on Consumer Behavior: The Mediating Role of Ascription of Responsibility and Attitude - El-Maghraby, Nada Hussam (AUC Knowledge Fountain, 2026)
The current study aims to examine the effect of environmental communication on promoting pro-environmental behaviors (PEBs) in the Egyptian society. The study also tests the mediating roles of ascription of responsibility and attitude toward pro-environmental behavior on the examined relationship. Another aim of the study is to explore intention as a mediator in the relationship between attitude toward pro-environmental behavior and behavior. The research is based on the Norm Activation Theory (NAT) and the Theory of Planned Behavior (TPB). A mixed-methods approach was implemented in this study. Quantitatively, a survey was conducted, and 406 responses were collected using convenience sampling method. In parallel, in-depth interviews were held to provide qualitative perspectives that complement the survey results. The findings reveal that environmental communication, which includes two dimensions, media exposure and word-of-mouth (WOM), significantly affects pro-environmental behavior directly and indirectly through ascription of responsibility and attitude toward pro-environmental behavior. The findings also indicate that attitude toward pro-environmental behavior has both a direct effect on pro- environmental behavior and an indirect effect mediated by intention. Age, level of education, and gender moderate the relationship between attitude toward pro-environmental behavior and pro-environmental behavior. Insights from the in-depth interviews confirm that environmental communication is one of the main contributors to engagement in pro- environmental behavior. In addition to presenting theoretical implications, the current study proposes practical implications for the public and private sector, NGOs, educators, and communication professionals in order to enhance environmental communication efforts in Egypt and promote pro-environmental behaviors.